Sustentabilidade e inclusão: estratégias de governamento na sociedade contemporânea de racionalidade neoliberal - Mohr, Alana Claudia (2018)
Several documents and guidelines have highlighted sustainability in articulation with inclusion as a guarantee for the development of both the population and the country. This thesis, which was carried out in the Research Line of Special Education, problematizes the emergence and functioning of the notion of sustainability in articulation with inclusion in Contemporaneity. Its main objective is to understand the way in which sustainability emerged as a discourse in the neoliberal rationality, thus functioning as a government device and enabling the strengthening of the inclusion imperative. Like inclusion, the notion of “sustainability” has become a recurrent term in several public policies and discourses both in Brazil and in the world. The documents selected to compose the research material refer to public policies; they include materials of Government programs, and both national and international documents and guidelines intended to present sustainability and inclusion actions, guidelines and principles. These materials were divided into three groups: inclusion policies; inclusion and sustainability; programs/partnerships. Grounded on Michel Foucault’s thought and Foucauldian Studies in Education, the analysis has relied on the analytical tool of government, as well as on transversal notions, biopolitics, neoliberalism and human capital. The analysis has enabled the understanding that sustainability in articulation with inclusion has been involved in the social development, since people have been regarded as the main target of the guarantee of an economically, politically and emotionally healthy life. In articulation, sustainability and inclusion have functioned as government strategies in the contemporary society of neoliberal rationality by investing in the development and productivity for social-productive inclusion in the marketplace games. Regarding people with disabilities, entrepreneurship, productivity and development of subjects as human capital are fundamental conditions for individuals to manage their lives by making the best choices and searching for in/exclusion situations in the market networks, thus contributing towards the development and security of the nation. The sustainability discourse operates the lifelong learning strategy from the inclusion perspective, in an attempt not to leave anybody out of either the neoliberal order or the economic game, so that nobody is left behind, and everybody becomes subjects of this time, in this order shaped through productivity and sustainability. By establishing partnerships and articulating social elements with education, sustainability has triggered actions to insert people with disabilities in the labor network (labor market) as both a condition and a possibility of their socialproductive development (social-productive inclusion) to guarantee the sustainable development of the nation and the security of the population. Therefore, the social-productive inclusion implies an intersectoral articulation and a look at human beings and their basic needs as a whole. The government, hence, attempts to foster the social-productive inclusion in parallel to the promotion of sustainable economic growth and development. Thus, the notion of social-productive inclusion emerges as not only the simple access to the market, but also as access to economic and social rights, which are fundamental for the sustainable development of the country.